CP-164 An audit of self-administration of medicines in cardiovascular wards and patient's preference for medicines administration while an inpatient. (25th February 2017) - Meilianti, S; Collings, V; Hafiz, I; Horne, R
Abstract : Background: Self-administration of medicines (SAM) is a transfer of patients' responsibility to manage their medication themselves. Studies show great value of SAM in increasing patient engagement, and improving patients' knowledge about medicines. As the UK's government encourages the implementation of SAM, this is a crucial first published study about an audit of SAM in cardiovascular wards. Purpose: To identify whether the SAM standards are being achieved, which are:(i) 100% of patients are offered the SAM programme;(ii) 100% of both informed consent and assessment forms are documented; and(iii) 100% of medicines are stored and labelled properly. To analyse the criteria which can encourage patients to participate in SAM. To provide evaluations for improvements in the SAM practices. Materials and methods: A 6 week prospective study was conducted in five cardiovascular wards. The study included finding eligible patients to participate in a structured interview and observing how the standards were being applied. A convenience sampling method was chosen with verbal consent for interviews. The questions covered were: (1) whether patients self-administered their medicines; (2) whether patients had been offered to self-administer; and (3) patients' preferences for administration (assessed using the Mann–Whitney, Kruskal–Wallis and χ 2 tests (significance level, p<0.05).Results Of the 422 patients interviewed, 22% self-administered their medicines. The findings were unsatisfactory since all wards did not achieve the target percentage. The average percentages were 4%, 10% and 21%, respectively. A total of 43% indicated a preference to self-administer while inpatients. This finding is similar to that of other studies, but has further analysed patients' preference. Younger people were significantly more willing to self-administer than older people. Those with a lower number of medicines were significantly more willing to self-administer than those with a higher number. Conclusion: This audit showed that the actual percentage was far from achieving the targets. This was mainly due to lack of awareness of the policy, and therefore there is a need to increase awareness of the policy. Some patients were interested in independently managing their medicines, particularly those who were younger or those taking fewer medicines. Further study could identify patients' and healthcare professionals' perspectives regarding the barriers to implementing this programme. References and/or acknowledgements: This work was funded by the Indonesia Endowment Funding for Education (LPDP). No conflict of interest